PRIORITIZING CONCUSSION PREVENTION IN YOUTH ICE HOCKEY: AN ASSESSMENT OF ENGLISH-LANGUAGE CANADIAN NEWSPAPERS AS A VEHICLE FOR EVIDENCE-BASED KNOWLEDGE TRANSLATION. Issue 7 (11th March 2014) - Blake, T; Rock, M; Emery, CA
Abstract : Background: The extent to which evidence-based injury prevention knowledge is conveyed to the public can have considerable impact on the implementation of injury prevention practice and policy change, which requires significant community engagement and mobilization. Media coverage has been shown to influence the amount of content regarding concussion on social media/networking sites, like Facebook© and Twitter©. Little is known about the extent to which news coverage of concussion reflects current evidence. Objective: To examine the extent to which English-language Canadian newspaper coverage reflects evidence-based messages regarding the relationship between body checking policy and the burden of concussion in youth ice hockey players. Design: Retrospective study using qualitative content analysis. Methods: News releases were collected for primary peer-reviewed research articles conducted through Canadian universities that evaluated the relationship between body checking policy and concussion among pediatric ice hockey players. Coverage of concussion and body checking in youth ice hockey was identified from the five English-language newspapers with the highest reported circulation figures from 2005 to June 2011. The presence of messages extracted from the news releases within the newspaper coverage was examined. Results: Five research articles and 33 newspaper items were included. One clinical message frame (i.e., concussions in youth ice hockey are a serious clinical problem) and one public health message frame (i.e., concussions in youth ice hockey are a cause for concern) were identified. Every newspaper item contained at least one of the evidence-based messages, and 31 out of 33 (94%) contained both messages. Conclusion: Evidence-based messages regarding the clinical and public health significance of concussion and the impact of body checking in youth ice hockey were accurately reported in Canadian newspaper coverage. The use of newspapers as a vehicle for knowledge translation would be a valuable addition to prevention implementation strategies requiring community engagement and support.